A bimodal γ′ phase precipitation in Ni–Al alloys with preaging and continuous cooling: phase-field simulation. (17th February 2021) - Chen, Xi; Li, Yongsheng; Yan, Zhengwei; Shi, Shujing; Wang, Dong; Lai, Kunwu; Chen, Jing
Abstract: A bimodal precipitation with primary and secondary γ ′ phase in Ni-17 at.% Al alloys was produced via preaging and continuous cooling. The morphology and composition evolution of γ ′ phase during cooling process were studied by using phase-field simulation, the bimodal precipitation mechanism was declared. The content of Al in secondary γ ′ phase is lower than the equilibrium composition because of the slower atom diffusion during continuous cooling. With the increase of cooling rates, the volume fraction and average radius of primary and secondary γ ′ phase are reduced, the number density of secondary γ ′ phase increases; in addition, the inter-distance of particle size distribution of primary and secondary γ ′ phase is widen. A long time of isothermal preaging reduces the precipitation and growth of secondary γ ′ phase. The hybrider precipitates with bimodal size distribution of γ ′ phase help optimizing the precipitates morphology of nickel based alloys.